Predicting shear failure in reinforced concrete members using a three-dimensional peridynamic framework. (1st January 2022) - Hobbs, Mark; Hattori, Gabriel; Orr, John
Highlights: Quantitative examination of the predictive accuracy of a 3D peridynamic model. Validation is performed against a series of nine reinforced concrete beams. The shear-span-to-depth ratio is systematically varied from 1 to 8. Many of the key features of shear and flexural failure are successfully captured. Discrepancies between the experimental and numerical results are examined. Abstract: The assumptions made in design codes can result in unconservative predictions of shear strength for reinforced concrete members. The limitations of empirical methods have prompted the development and use of numerical techniques. A three-dimensional bond-based peridynamic framework is developed for predicting shear failure in reinforced concrete members. The predictive accuracy and generality of the framework is assessed against existing experimental results. Nine reinforced concrete beams that exhibit a wide range of failure modes are modelled. The shear-span-to-depth ratio is systematically varied from 1 to 8 to facilitate a study of different load-transfer mechanisms and failure modes. A comprehensive validation study such as this has until now been missing in the peridynamic literature. A bilinear constitutive law is employed, and the sensitivity of the model is tested using two levels of mesh refinement. The predictive error between the experimental and numerical failure loads ranges from +3% to −57%, highlighting the importance of validation against a series of problems. The results demonstrate that the model captures many of the factors that contribute to shear and bending resistance. New insights into the capabilities and deficiencies of the peridynamic model are gained by comparing the expected load-transfer mechanisms with the predictive error.